(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research lies in relying on scientific foundations in finding standard degrees and levels in terms of the muscular physical pattern of some offensive skills for young basketball players. For players and at the level of some offensive skills of young basketball players, as well as finding the grades and standard levels of offensive skills in terms of the muscular physical pattern of young basketball players.The researcher used the descriptive approach in the survey method to suit the nature of the research problem. As for the research community, it included the Iraqi youth club players participating in the 2021-2022 season, and their number is 128 players. The researcher found the physical patterns that the research community divided into (muscular pattern - pattern). The skinny - and the obese style) and then the offensive skills were determined, as they were represented by (chest handling - dribbling by changing direction ¬_ peaceful shooting - jumping shooting) and their tests and application on the research sample of 43 players who represent the muscular style, The T-standard grades were determined and standard levels were set for tests of some offensive skills for young basketball players.